Monitoring of training and recovery in elite cross-country skiers - Pulkkinen, Wayland John (My University, 1996)
The purpose of this investigation was to monitor and assess the training program of elite cross-country skiers over an eight week period in order to develop a comprehensive profile of elite crosscountry skiers. This was performed by: i) observing the training responses of skiers over time to physiological, biochemical and performance variables; ii) examining the relationship between the Overstress Monitoring Inventory to both resting values of heart rate and blood pressure; iii) observing the contrasting effects of physiological, biochemical and performance variables over a four and eight day period of reduced training. Ten (8 male, 2 female) elite cross-country skiers (19-27 yrs.) participated in the study and performed endurance training 10-24 hours per week. Following eight weeks of training, subjects were divided into two groups (N=4, N=6), and reduced training volume by 50% for four and eight days respectively. Physiological measurements consisted of evaluating peak and threshold (at TLac) VO2 resting heart rate and blood pressure, blood lactate, lactate threshold (TLac), maximal heart rate, heart rate at TLac, %V02 (at TLac), %VO2 at OBLA (onset o f blood lactate accumulation) and treadmill time to exhaustion. Biochemical measurements consisted of evaluating white and red blood cell count, hematocrit, hemoglobin, serum ferritin, serum urea, creatine phosphokinase (CPK), lactate dehydrogenase (LDH), cortisol and testosterone. Psychological measurements were assessed with the use of a 29 question inventory prepared by Cross-country Canada. Performance evaluations consisted of both a mini timing study and technique analysis. Subjects were required to ski using the free techniques a 5 km course and were videotaped while skiing for one complete cycle (pole plant to pole plant) up a 5% grade for 30 meters. Tapes were then digitized using the peak 2D system and analyzed for kinematic parameters of cycle rate, time and length. Significant differences were found in maximal heart rate (p < 0.05) and hemoglobin (p < 0.01) levels following 4 and 8 weeks o f endurance training, respectively. Mean values of CPK decreased significantly (p < 0.05) following 4 weeks of training. Cortisol concentrations demonstrated an increasing trend throughout 8 weeks of training, however, no significant variations (p < 0.05) were observed during training or between groups following 4 and 8 days of reduced training. Testosterone levels profiled a similar response as cortisol, however, marked variations (p < 0.05) between groups after 4 and 8 days reduced training were demonstrated. Treadmill time to exhaustion increased significantly (p < 0.05) following 8 days of reduced training, although mean race time decreased following 4 days of reduced training. Mean scores of kinematic parameters failed to identify any significant variations throughout the period of the investigation. Similarly, correlational examination of the stress inventory and resting systolic blood pressure and heart rate also failed to illustrate any particular trends throughout the study. It was concluded that the elite skiers examined in the study demonstrated improvements in physiological, biochemical and performance evaluations following 8 weeks o f endurance training. Specifically, 8 days of reduced training (a 50% decrease in training volume) illustrated a greater improvement in physiological, biochemical and performance evaluations when compared to 4 days of reduced training.
Keywords: Cross-country skiing Training; Cross-country ski racing Training